Peripheral Nerve Schwannomas: A Literature Review - Magalhães, Marcelo José Silva; Pereira, Douglas Vitor Maia; Oliva, Henrique Nunes Pereira; Durães, Dayane Tabatha Santos; Caiado, Fernanda Leal; Araújo, Grazielle Mendes; Freitas Junior, Enilton Teixeira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Introduction Schwannomas are benign tumors originating from the cells, which wrap around axons that are usually encapsulated and solitary. These tumors usually lead to little or no symptomatology. They are usually the most common peripheral nerve tumors in adults, with their highest incidence between the third and fifth decades of life.Objective To perform a review about schwannoma of the peripheral nerves, presenting its definition, epidemiology, diagnosis, symptomatology and treatment.Methodology This is a descriptive work, based on a review of articles available in the PubMed database with the descriptors schwannoma and peripheral nerves.Results and Discussion Only papers published between 1981 and 2019, describing studies in humans, and that were available as full articles were selected. A total of 391 articles were included; after reading the titles, we noted that 67 articles fit the topic of the present study. Among the articles selected for reading, 33 fit the objectives of the present work, and were considered for the writing of the present article.Conclusion Schwannomas are benign myelin sheath tumors that develop with local symptomatology or asymptomatic and present a good surgical prognosis with generally reduced rates of surgical complications.
Keywords: schwannomas; peripheral nerves; neuroanatomy; neurosurgery